Development of MAMEYA Interactive Learning Media to Improve Students’ Critical Thinking Skill at Elementary School - Fara Khoirun Nisa'; Yulina Ismiyanti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to develop an interactive learning media called MAMEYA (Mari Mengenal Gaya) to improve students' critical thinking skills. The method used is R&D (Research and Development) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this research were all 25 fourth-grade students of SD Negeri Tempuran 1. Data collection techniques used validation questionnaire instruments, response questionnaires, and test questions. Questionnaire data analysis used descriptive categorical and percentage techniques. At the same time, the test data analysis used a paired sample T-test and the N-Gain test, which had previously carried out a data normality test as a prerequisite test. The research results showed that the validation (feasibility) assessment obtained very feasible criteria with a score of 90% from the media aspect, 93% from the material aspect, and 87% from the language aspect. The practicality assessment obtained very practical criteria based on the response value given by the teacher of 97% and students of 89%. The effectiveness assessment was obtained by calculating the data normality test with a Sig. value pre-test 0.079 and post-test 0.850 > 0.05, which shows that the data of the students' test assessment results are normally distributed. The calculation of the paired sample T-test obtained a Sig. (2 tailed = 0.000) < 0.05, which means that MAMEYA interactive media affects students' critical thinking skills. At the same time, the N-Gain test obtained a value of 0.6644 with a moderate category, which shows an increase in critical thinking skills after using MAMEYA interactive media. It is concluded that MAMEYA interactive media can be feasible, practical, and effective in improving critical thinking skills and facilitating better student understanding.